The absence of telomerase leads to immune response and tumor regression in zebrafish melanoma - Bruno Lopes-Bastos; Joana Nabais; Tânia Ferreira; Giulia Allavena; Mounir El Maï; Malia Bird; Seniye Targen; Lorenzo Tattini; Da Kang; Jia-Xing Yue; Gianni Liti; Tânia G. Carvalho; et al. (Cell Reports)
Summary: Most cancers re-activate telomerase to maintain telomere length and thus acquire immortality. Activating telomerase promoter mutations are found in many cancers, including melanoma. However, it is unclear when and if telomerase is strictly required during tumorigenesis. We combined the telomerase mutant (tert−/−) with two established zebrafish melanoma models. We show that tert−/− melanomas initially develop with similar incidence and invasiveness to tert+/+ tumors. However, they eventually decline in growth and regress. Late tert−/− tumors exhibit reduced cell proliferation, increased apoptosis, and melanocyte differentiation. Notably, these tumors show enhanced immune cell infiltration and can resume growth when transplanted into immunocompromised hosts. We propose that telomerase is required for melanoma in zebrafish, albeit at later stages of progression, to sustain tumor growth while avoiding immune rejection and regression. Thus, the absence of telomerase restricts melanoma through tumor-autonomous mechanisms (cell-cycle arrest, apoptosis, and melanocyte differentiation) and a non-tumor-autonomous mechanism (immune rejection).